Anxiety, stress level and fear as the predictors of life satisfaction among working adults in Malaysia during the pandemic of COVID-19 - Lee, Jing Yean; Tan, Sheng Shan; Lee, You Wei (2021)
This study was about anxiety, stress level and fear towards COVID-19 as predictors to predict life satisfaction, and whether predictors were able or unable to affect life satisfaction during the pandemic of COVID-19 among working adults in Malaysia. A total 112 working adults participants in Malaysia participated in this study. Utilizing convenience sampling method by distributing online questionnaires through WhatApps, Facebook and others to collect data from target participants. Online questionnaire created by Qualtrics online platform with four scales which were Satisfaction with Life Scale (SWLS), Beck Anxiety Inventory (BAI), Perceived Stress Scale-10 (PSS-10), and Fear of COVID-19 Scale (FCV-19S). Number of female participants were 57 and male participants were 55 that included Malay, Chinese and Indian. The results showed no significant prediction of anxiety, stress and fear towards COVID-19 to predict life satisfaction among working adults during the pandemic of COVID-19 through multiple linear regression. This study showed not similar results with previous study as no significant prediction of anxiety, stress and fear towards COVID-19 to predict and affect life satisfaction among working adults in Malaysia during the pandemic of COVID-19. The results of this study can be used as a source of information to help provide information that is related in Malaysia and for future research.